Alamandine abrogates neutrophil degranulation in atherosclerotic mice. (4th January 2017) - Da Silva, Analina R.; Lenglet, Sébastien; Carbone, Federico; Burger, Fabienne; Roth, Aline; Liberale, Luca; Bonaventura, Aldo; Dallegri, Franco; Stergiopulos, Nikolaos; Santos, Robson A. S.; Mach, François; Fraga‐Silva, Rodrigo A.; et al.
Abstract: Background: Neutrophil‐mediated inflammation was recently identified as an active contributor to athero‐progression. Therapeutic strategies inhibiting neutrophil degranulation or recruitment were hypothesized to positively impact on plaque vulnerability. In this study, we investigated whether treatment with the recently discovered agonist of the Mas‐related G‐coupled receptor type D (MrgD) alamandine would impact on neutrophil degranulation in vivo and in vitro . Materials and methods: Fifteen‐week‐old ApoE −/− mice were fed with a Western‐type diet for an additional 11 weeks. After the first 2 weeks of diet, mice were surgically implanted with a carotid 'cast' device that alters the blood shear stress and induces different carotid plaque phenotypes. During the last 4 weeks before euthanasia, mice were randomly assigned to subcutaneously receive vehicle (NaCl 0·15 M) or alamandine (24 μg/kg/h) by micropump. For in vitro experiments, neutrophils were obtained after thioglycollate intraperitoneal injection in ApoE −/− mice. Results: Treatment with alamandine was well‐tolerated, but failed to affect lipid, macrophage, neutrophil or collagen content within carotid and aortic root plaques. Also, treatment with alamandine did not affect Th‐cell polarization in lymphoid organs. Conversely, alamandine administration was associated with a reduction in serum levels of neutrophil granule enzymes, such as MMP‐9 and MPO as well as MMP‐9 content within aortic root plaques. In vitro, preincubation with alamandine dose‐dependently abrogated PMA‐induced neutrophil degranulation of MMP‐9 and MPO. Conclusion: These results suggest that treatment with the MrgD agonist alamandine led to a reduced release of neutrophil granule products, potentially interfering with pro‐atherosclerotic neutrophil activation.